Mentors' approach to practicum mentoring in the Spanish and Thai contexts: a two-cohort comparison using the Mentoring Profile Inventory. Issue 2 (10th April 2020) - Mena, Juanjo; Faikhamta, Chatree; Clarke, Anthony
Abstract : Purpose: The purpose of this study was to better understand the work of mentors or cooperating teachers (CTs) in Spain and Thailand, by comparing how mentors in both contexts conceive of their work in teacher education. Design/methodology/approach: A comparative study based on a crossnational research (CNR) approach was used. An internationally validated instrument, the Mentoring Profile Inventory (MPI), was given to 171 Spanish and 170 Thai CTs, and an analysis using t tests and constant comparative methods was conducted. Findings: The main results indicate that the Spanish cohort reported being significantly more challenged than their Thai counterparts in working with preservice teachers (PSTs). Both groups indicated a similar degree of motivation. The comparative analysis revealed that the Thai CTs emphasized the importance of ethics in teaching and being a role model for PSTs, whereas the Spanish CTs emphasized the need for strong interpersonal relationships as being central to successful mentoring. Research limitations/implications: Understanding mentors' challenges and motivations can form the basis for reflecting upon the essential components of teacher preparation in both contexts. Furthermore, comparative cross-context analyses, as demonstrated in this paper, are vital for the identification of important differences that might otherwise remain invisible or unrecognized from a single-context perspective. Originality/value: The study is original in its focus in that it offers insights that help better understand attitudes and performance within and across contexts – in this case, a European and an Asian country – using a common metric, the MPI. This study serves as an exemplar for other comparison studies for countries of mentors.